Utilization of the phyphox application (physical phone experiment) to calculate the moment of inertia of hollow cylinders - Yasaroh, Sabila; Kuswanto, Heru; Ramadhanti, Desi; Azalia, Aisha; Hestiana, Hestiana (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Experiments have been carried out on determining the value of the moment of inertia of a hollow cylinder. This study aims to analyze the value of the moment of inertia with variations in the radius of the hollow cylinder using the Phyphox Application (Physical Phone Experiment). This research is experimental. The tools and material used area 1-meter longboard, three hollow cylinders with different radius sizes but the same mass, smartphone, laptop, caliper, and balance.The experiment of rolling motion on a hollow cylinder on an inclined plane is assisted by data processing in a Phyphoxapplication. From the experiment, the result of the moment of inertia value from data processing is 4.89 x 10-4kg.m2, 9.82 x 10-4kg.m2, 12.4 x10-4kg.m2. This research can be used as a teacher reference in teaching the topic of moments of inertia in physics learning at school. This is highly recommended for distance learning during the pandemic so that mastery of concepts is maximized. Further research is suggested that it can be tried to use other materials with other types of rigid bodies to find the moment of inertia. Further references on digital application media to assist learning are also needed considering the dynamic development of technology.